Effect of ultrasonic treatment on the surface hydrophobicity of pyrite: Properties and mechanism of ultrasonic products - Lin, Qiqiang; Sun, Lei; Cao, Yang; Xiang, Meitao; Guo, Yuanhao; Gao, Zhiyong; Xie, Jie; Sun, Wei (Minerals engineering, 2025)
[Display omitted] •Ultrasonic-generated Fe ions and suspended substances reduce pyrite hydrophobicity.•Fe2+ oxidation to Fe3+ via dissolved oxygen consumption enhances pyrite oxidation.•Suspended substances outcompete pyrite in sodium butyl xanthate adsorption.•The hydrophobicity of pyrite is poor in ultrasonic pulp but remains good in clean pulp.•The phenomenon of ultrasonic products of pyrite was first proposed and studied. The conventional depression of pyrite via excessive lime addition in flotation systems leads to persistent mineral residues in tailings, while simultaneously hindering timely reactivation for recovery. These residual pyrite-bearing tailings undergo progressive oxidative dissolution when exposed to meteoric water, inducing acid mine drainage generation through sustained proton release. Ultrasonic treatment and its derived products were found to effectively inhibit pyrite, eliminating the requirement for high lime dosages. In this study, pyrite was selected as the research subject to investigate the effects of ultrasonic products on their hydrophobicity—specifically, whether the removal of dissolved Fe2+ and Fe3+ ions and suspended substances in the turbid pulp after ultrasonic treatment affected the hydrophobicity of the pyrite surface. The experimental results indicated that the ultrasonic pulp contained 6.94 × 10-3 mol/L of Fe2+ and 5.42 × 10-3 mol/L of Fe3+, which facilitated the oxidation of pyrite. This process not only increased the proportion of Fe(III) on the pyrite surface but also led to the formation of hydrophilic precipitation of SOn2-, thereby reducing the hydrophobicity of pyrite. Additionally, the suspended substances in the ultrasonic pulp preferentially interacted with the collector, sodium butyl xanthate, hindering its adsorption on the surface of pyrite and exacerbating the reduction in hydrophobicity. Ultrasonic-generated Fe ions and suspended substances reduce pyrite hydrophobicity.